2018
DOI: 10.1016/j.drugalcdep.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alcohol use associated with changes in HIV disease severity over time: A national longitudinal study in the Veterans Aging Cohort

Abstract: Improvement in HIV severity was greatest among PLWH with relatively stable drinking, most of whom initially did not drink or drank at low levels. Those with large changes (especially increases) in drinking appear at greatest risk for poor HIV control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Furthermore, though alcohol screening is prompted by clinical reminders routinely in VA primary care settings, their use may be more variable across rurality and in infectious disease and/or HIV clinics where veterans with HIV may receive much of their care, especially in rural settings. Although a previous study conducted in a national sample of VA outpatients found that over 90% of patients received an annual screen, and 1 study in a sample of VA patients with HIV found that 87% received at least 1 annual AUDIT‐C screen during the study period, differences in screening rates across rurality have not been described among PLWH. If veterans living with HIV in rural areas are less likely than their urban counterparts to receive alcohol screening, then alcohol use may be undercaptured among PLWH living in rural areas.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, though alcohol screening is prompted by clinical reminders routinely in VA primary care settings, their use may be more variable across rurality and in infectious disease and/or HIV clinics where veterans with HIV may receive much of their care, especially in rural settings. Although a previous study conducted in a national sample of VA outpatients found that over 90% of patients received an annual screen, and 1 study in a sample of VA patients with HIV found that 87% received at least 1 annual AUDIT‐C screen during the study period, differences in screening rates across rurality have not been described among PLWH. If veterans living with HIV in rural areas are less likely than their urban counterparts to receive alcohol screening, then alcohol use may be undercaptured among PLWH living in rural areas.…”
Section: Discussionmentioning
confidence: 92%
“…Our data suggest that a reduction in drinking to less than unhealthy levels can result in improved HIV‐related clinical outcomes for women, regardless of the specific medication used. While other observational data from clinical trials or longitudinal cohorts have shown increases in drinking to be associated with worse HIV clinical outcomes, little evidence suggests that reductions in drinking are associated with improved HIV‐related outcomes such as HIV viral suppression (Barai et al., ; Williams et al., ). One challenge with traditional longitudinal alcohol studies is that persons may reduce drinking because they have become sicker, causing it to appear that quitting drinking may be more harmful than beneficial (Williams et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is also associated with chronic disease outcomes that are more common in persons with HIV, including liver disease, cardiovascular disease, and cancer (Cao et al., ; Gao and Bataller, ; Kelso et al., ; Park et al., ; Smith et al., ). Longitudinal studies suggest that increases in drinking among WLWH can result in worse HIV‐related clinical outcomes (Barai et al., ; Williams et al., ). However, little hard evidence suggests that reductions in drinking will correlate with improved HIV‐related health outcomes.…”
mentioning
confidence: 99%
“…In the national Veterans Health Administration (VA)—the largest integrated health care system in the US—delivery of both alcohol screening (to identify patients with unhealthy alcohol use) and brief intervention (for those screening positive for unhealthy alcohol use) are incentivized by national performance measures . The vast majority of VA outpatients is annually screened for unhealthy alcohol use with the 3‐item Alcohol Use Disorders Identification Test Consumption (AUDIT‐C), including patients with HIV . And, though not incentivized by performance measures, specialty addictions treatment and AUD medications are recommended in VA's clinical guideline for treatment of substance use disorders and routinely monitored as part of quality improvement .…”
mentioning
confidence: 99%
“…4,20,21 The vast majority of VA outpatients is annually screened for unhealthy alcohol use with the 3-item Alcohol Use Disorders Identification Test Consumption (AUDIT-C), 21 including patients with HIV. 22 And, though not incentivized by performance measures, specialty addictions treatment and AUD medications are recommended in VA's clinical guideline for treatment of substance use disorders and routinely monitored as part of quality improvement. 23 The VA is also the largest provider of HIV care in the United States.…”
mentioning
confidence: 99%